Bridging the digital divide: exploring undergraduate students’ experiences with learning management systems in a rural South African University - Ajani, Oluwatoyin Ayodele (Frontiers in Education, 2025)
IntroductionThis study drew on the Unified Theory of Acceptance and Use of Technology (UTAUT) to explore the perceptions, challenges, and opportunities associated with the use of learning management systems (LMSs) by undergraduate students of a rural South African university. The research aimed to understand how infrastructural, cultural, and pedagogical factors fostered engagement with LMSs among students, considering the digital divides and socio-economic disparities within the environment.MethodsThe study employed an interpretive qualitative approach as part of a broader mixed-methods study that is currently awaiting approval. Data were collected through semi-structured interviews with 40 purposively sampled undergraduate students from four faculties. Thematic analysis, guided by the UTAUT framework, was conducted to identify patterns in students’ experiences.ResultsThe findings revealed that while students identified the opportunity for learning flexibility and access through the LMS, their experience was primarily shaped by infrastructural limitations, gaps in digital literacy, and variation in the level of engagement by faculty. Effort expectancy and facilitating conditions emerged as determinants of LMS uptake. Cultural perceptions and social influence also contributed to shaping students’ attitudes toward LMS use.DiscussionBeyond the study’s findings lies the assertion for institutional interventions targeting the rural digital divide in tertiary education. These interventions include improvements to digital infrastructure, training both students and faculty, and integrating LMS with culturally responsive pedagogies for equitable and meaningful use of technology. These findings will enter the arena of discourse on inclusive digital education and aid in policymaking and practice within under-resourced educational settings.